Knowledge and practices about massage and hygienic practices of mothers regarding infant care in Lucknow - Khanna, Anish; Gupta, Pratibha (International Journal Of Community Medicine And Public Health, 2017)
Background: Children are our future and our most precious resources. Health of the future children’s depends on the nurturing practice adopted by the family. The first four weeks of life constitute the “neonatal period”. The ideal basic needs for any new born includes breathing, warmth, cleanliness, and feeding mothers milk. The objective was to study knowledge and practices about massage and hygienic practices of mothers regarding infant care in Lucknow. Methods: Study Population: The present study was carried out amongst infants in urban areas of Lucknow city. Study unit was infant. An infant in present study was defined as a child aged less than 1 year of age. Study design: The present study was a Hospital-based cross-sectional study. Study Period: 6 months, July 2016 to December 2016. Sample Size: A total of 262 Infants were included in the study. Interview was taken from mothers of infants child attending OPD at a tertiary care Hospital in Lucknow city. Results: A total of 262 infants were included in the study. There were 139 (53%) male children and 123 (47%) female children. In the present study majority (92.7%) of mothers cleaned their baby with water after it passed stools and washed their hands with soap and water (72.5%) after cleaning stools. Majority (81.6%) of the mothers were of the opinion that bones of the baby become strong after massage. Body massage was practiced in 92.4% of neonates Mustard oil was used by 60.4% mothers for massage of the neonates about 1/3rd of the mothers (37.2%) used Dabur red oil for massaging the neonates. Conclusions: In present study majority of the mothers had correct knowledge and practices regarding massage and its benefit and about hygienic practices regarding handling of faeces and hand washing after cleaning of stool.